In vitro -Osteoclastic Activity Studies on Surfaces of 3D Printed Calcium Phosphate Scaffolds - Detsch, Rainer; et al. (Journal of Biomaterials Applications, 2011)
Various biomaterials have been developed for the use as bone substitutes for bone defects. To optimize their integration and functionality, they should be adapted to the individual defect. Rapid prototyping is a manufacturing method to tailor materials to the 3D geometry of the defect. Especially 3D printing allows the manufacture of implants, the shape of which can be designed to fit the bone defect using anatomical information obtained from the patient. 3D printing of calcium phosphates, which are well established as bone substitutes, involves a sintering step after gluing the granules together by a binder liquid. In this study, we analyzed if and how these 3D printed calcium phosphate surfaces can be resorbed by osteoclast-like cells. On 3D printed scaffold surfaces consisting of pure HA and Β-TCP as well as a biphasic mixture of HA and TCP the osteoclastic cell differentiation was studied. In this regard, cell proliferation, differentiation, and activation were analyzed with the monocytic cell line RAW 264.7. The results show that osteoclast-like cells were able to resorb calcium phosphate surfaces consisting of granules. Furthermore, biphasic calcium phosphate ceramics exhibit, because of their osteoclastic activation ability, the most promising surface properties to serve as 3D printed bone substitute scaffolds. © 2010 The Author(s).
Keywords: 3D printing; bone reconstruction; calcium phosphate ceramics; osteoclast development; resorption